(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the business sustainability of the food industry in selected micro-enterprises in Brgy Sta. Monica Quezon City in terms of responsibility, accountability, compliance, reliability, responsiveness, and assurance; the significant relationship between sustainability and performance in terms of aforecited variables; problem encountered of selected micro-enterprise and recommendation to address the following techniques to develop more or maintain the business sustainability. The result of this study reveals that the business sustainability of the food industry is evaluated as Always in terms of responsibility and accountability, and the Performance of sustainability is evaluated as Excellent performance in terms of compliance, reliability, responsiveness, and assurance; the problem encountered of selected micro-enterprise is the inflation rate, lack of capital or cash flow, lack of proper marketing and too many competitors the techniques to develop more or maintain the business sustainability is to develop a unique marketing strategy and stay ahead in terms of quality, price and customer service. This study recommends a developing strategy to compete with competitors, develop a unique marketing strategy, and stay ahead in terms of quality, price, and customer service.